Analyzing the effect of the COVID-19 vaccine on Parkinson’s disease symptoms - Sabat, Revati; Dayton, Orrin L.; Agarwal, Amit; Vedam-Mai, Vinata (Frontiers in Immunology, 2023)
Background: Parkinson’s Disease (PD) is one of the most common neurodegenerative diseases. PD has recently received more attention by researchers in the midst of the COVID-19 pandemic. Objective: Yet to be researched is the effect of the COVID-19 vaccines on PD patients. Several PD patients are still hesitant to the vaccine due to this unaddressed fear. The purpose of this study is to address this gap. Methods: Surveys were administered to PD patients 50 years and older at UF Fixel Institute who received at least one dose of the COVID-19 vaccine. Survey questions included patients’ severity of PD symptoms before and after the vaccine and extent of worsening PD symptoms post-vaccination. After three weeks of collecting responses, the data was analyzed Results: 34 respondents were eligible for data consideration because they fell within the age range being studied. A total of 14 respondents out of 34 (41%, p=0. 0001) reported that their PD symptoms worsened after the COVID-19 vaccine to some extent. Conclusion: There was strong evidence of worsening of PD symptoms post COVID-19 vaccination, however it was mostly mild and limited to a couple of days. The worsening had statistically significant moderate positive correlation with vaccine hesitancy and post-vaccine general side effects. A possible causative mechanism of PD symptom worsening using existing scientific knowledge would be stress and anxiety associated with vaccine hesitancy and the extent of post-vaccine general side effects (fever, chills, pain), likely via simulating a mild systemic infection/inflammation the latter already established causes of PD symptom worsening.